2014
DOI: 10.1155/2014/658913
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Adiponectin Role in Obesity and Obesity-Related Diseases

Abstract: Obesity is a major health problem strongly increasing the risk for various severe related complications such as metabolic syndrome, cardiovascular diseases, respiratory disorders, diabetic retinopathy, and cancer. Adipose tissue is an endocrine organ that produces biologically active molecules defined “adipocytokines,” protein hormones with pleiotropic functions involved in the regulation of energy metabolism as well as in appetite, insulin sensitivity, inflammation, atherosclerosis, cell proliferation, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
385
2
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 486 publications
(419 citation statements)
references
References 160 publications
(199 reference statements)
13
385
2
19
Order By: Relevance
“…However, in contrast with earlier animal and human reports (18, 19), we did not see any significant effect of diet therapy on the HOMA-IR score. Adiponectin is an insulin-sensitizing adipocytokine that paradoxically decreases in obese and diabetic patients (20). Our results showed a significant increase in circulating levels of adiponectin in obese patients under the diet therapy, confirming some earlier reports (18,21,22).…”
Section: Discussionsupporting
confidence: 91%
“…However, in contrast with earlier animal and human reports (18, 19), we did not see any significant effect of diet therapy on the HOMA-IR score. Adiponectin is an insulin-sensitizing adipocytokine that paradoxically decreases in obese and diabetic patients (20). Our results showed a significant increase in circulating levels of adiponectin in obese patients under the diet therapy, confirming some earlier reports (18,21,22).…”
Section: Discussionsupporting
confidence: 91%
“…Nigro et al, observed that adiponectin has essential role in therapies for the anticipation and/or for the management of obesity and obesity associated diseases such as antihyperglycemic, antiatherogenic, and antiinflammatory properties. [30] Adiponectin has protective role in cardiovascular health also. In a recent review, it has been summarized that after understanding of role of adiponectin in cardiovascular health, it is useful for determination of and Polyphen (P < 0.0001 ) which is based on the damages or deleterious amino acid substitution for HSL gene receptor and post-receptor signaling process that induces the cardiovascular protective role of adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…In accompany with this, phosphorylation of acetyl coenzyme A carboxylase (ACC), fatty-acid oxidation, glucose uptake and lactate production in myocytes, and phosphorylation of ACC and reduction of molecules involved in gluconeogenesis in the liver were observed, which eventually led to reduction of glucose levels in vivo [41]. Moreover, adiponectin can directly act on inflammatory cells and suppresses reactive oxygen species which in turn stimulates the expression of the anti-inflammatory cytokine IL-10, and suppresses the NF-κB inflammatory signaling pathway, and downregulates the key inflammatory cytokine TNF-α [42,43]. Protection against cardiovascular diseases by adiponectin is achieved by its actions on various cell types in cardiovascular system, including endothelial cells, macrophages/monocytes, smooth muscle cells, cardiac muscle cells and etc.…”
Section: Hypoadiponectinemia and Metabolic Syndromesmentioning
confidence: 99%